The cost of demand creation activities and voluntary medical male circumcision targeting school-going adolescents in KwaZulu-Natal, South Africa. - Gavin George; Michael Strauss; Elias Asfaw (PLoS ONE)
Background Voluntary medical male circumcision is an integral part of the South African government's response to the HIV and AIDS epidemic. However, there remains a limited body of economic analysis on the cost of VMMC programming, and the demand creation activities used to mobilize males, especially among adolescent boys in school. This study addresses this gap by presenting the costs of a VMMC program which adopted two demand creation strategies targeting school-going males in South Africa. Methods Cost data was collected from a VMMC program in the KwaZulu-Natal province of South Africa. A retrospective, micro-costing ingredient approach was applied to identify, measure and value resources of two demand creation strategies targeting young males. Results The program circumcised 4987 young males between May 2011 and February 2013, at a cost of $127.68 per circumcision. Demand creation activities accounted for 32% of the total cost, HCT contributing 10% with the medical circumcision procedure accounting for 58% of the total cost. Using the first demand creation strategy, 2168 circumcisions were performed at a cost of $149.57 per circumcision. Following this first strategy, a second demand creation strategy was adopted which saw the cost fall to $110.85 per circumcision. More young males were recruited following the second strategy with clinic services more efficiently utilized. Whilst the cost per circumcision of demand activities rose slightly between the first ($39.94) and second ($41.65) strategy, there was a substantial reduction in the cost of the circumcision procedure; $90.01 under the first strategy falling to $60.60 following the adoption of the second demand creation strategy. Conclusion Ensuring the optimal use of clinic facilities was the primary driver in reducing the cost per circumcision. This VMMC program has illustrated the value of evaluating progress and instituting changes to attain better cost efficiencies. This adjustment resulted in a substantial reduction in the cost per circumcision.